The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2460/javma.235.2.194
|View full text |Cite
|
Sign up to set email alerts
|

Use of phlebotomy treatment in Atlantic bottlenose dolphins with iron overload

Abstract: Although the cause of the iron overload and high serum aminotransferase activities remained unknown, phlebotomy treatment successfully resolved the clinicopathologic abnormalities, supporting a role of iron overload in the hepatopathy of the 3 dolphins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 21 publications
2
37
0
Order By: Relevance
“…Within the fasting samples, ALT and GGT were significantly higher in the iron overload group ( p  = 0.0159 and 0.0476, respectively) while MCHC was significantly lower (Table S2 in Supplementary Material; p  = 0.0317) compared to controls. Iron was not significantly different, which was expected since the iron overload samples were taken post-phlebotomy (21). Within the post-prandial set, ALT was also higher and MCHC (Table S2 in Supplementary Material) was lower in the iron overload group ( p  = 0.0159 and 0.0159, respectively) compared to controls.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Within the fasting samples, ALT and GGT were significantly higher in the iron overload group ( p  = 0.0159 and 0.0476, respectively) while MCHC was significantly lower (Table S2 in Supplementary Material; p  = 0.0317) compared to controls. Iron was not significantly different, which was expected since the iron overload samples were taken post-phlebotomy (21). Within the post-prandial set, ALT was also higher and MCHC (Table S2 in Supplementary Material) was lower in the iron overload group ( p  = 0.0159 and 0.0159, respectively) compared to controls.…”
Section: Resultsmentioning
confidence: 63%
“…Iron overload cases in this study were previously reported to have chronically elevated serum aminotransferases, specifically alanine aminotransferase (ALT) and aspartate aminotransferase (AST), as well as elevated serum iron (20). These four case animals had since undergone phlebotomy treatments in order to manage iron overload, and diagnoses of iron overload have been confirmed by live liver biopsies in three of the four animals (21). Control animals had normal blood values throughout the year before sample collection, specifically iron, ALT, and AST, based upon published reference ranges for healthy bottlenose dolphins (22).…”
Section: Methodsmentioning
confidence: 89%
“…The case dolphin had a clinical history of chronic, high liver enzymes (alanine transaminase >42 U/L, aspartate transaminase >263 U/L, and gamma-glutamyl transpeptidase >44 U/L) and serum iron that began at the age of 25 years and peaked at 42 years [Figure 1A; (23)]. A liver biopsy at that time demonstrated that this dolphin had diffuse, moderate hemosiderosis, mild multifocal vacuolar degeneration, mild amounts of granular intracellular iron in hepatocytes, and moderate amounts of intracellular iron visualized via staining in the Kupffer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Veterinarians can now also consider stem cell therapy when evaluating the treatment options for common dolphin diseases such as corneal trauma and liver disease, both of which have shown promising therapeutic benefits with stem cell treatment in humans [31,32]. Several dolphin diseases have similar human counterparts, including type 2 diabetes [8], urate nephrolithiasis with renal failure [33], and iron overload with liver disease [9,34]. The dolphin may serve as a human model for several disease processes, as was recently proposed for type 2 diabetes [10] and aging studies [35], where new treatment modalities using stem cells could be realized.…”
Section: Discussionmentioning
confidence: 99%